(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we consider a quasilinear elliptic eigenvalue problem. For the unbounded coefficients, we allow the eigen exponent greater than the Sobolev imbedding critical exponent; for the equations, we also allow the coefficient of suitable smallness condition greater than 1.